(untitled) (Research, Society and Development, 2019)
The aim of this article is to analyze the scientific production surrounding the term "Society, Environment and Health" through a bibliometric study, with bibliographical and documentary research, and a conceptual discussion that transpasses the theme in its social, economic context and environmental . In the effort to identify what has already been published about air pollution and its effects on the health of children in the Brazilian Amazon, we analyzed from 2010 to 2018, articles and other documents that contained, in addition to the words "Climate Change" or "Climate Change "," Climate Modeling "or" Climate Modeling "" Burned "or" Burned "," Air Pollution "or" Air Pollution "," Health "or" Health "and" Brazil "or" Brazil " , keywords and / or the introduction, terms associated with the main macro-theme, such as: "society", "environment" and "health". The bibliographic sources of research were the platforms: Medical Literature Analysis and Retrieval System Online (MEDLINE / PUBMED) and Dimensions Portal, which is part of the " Part of the Digital Science (international level); Scientific Electronic Library Online (SciELO) and Portal de Periodical Capes (national level) and at the local level, at the Lourenço José Tavares Vieira da Silva Library (TCC and Dissertation), at the PROPED (Research Projects) and PROEX (Projects and Extension Programs) and in the official page of the undergraduate and graduate courses, analyzing the subjects (compulsory and elective) governed by the PPC’s of the Federal Rural University of Amazonia - Campus Parauapebas-PA. The analysis included 178 articles at the international level, 59 articles at the national level, and finally at the local level, 20 research projects, 5 extension projects, 1 extension program and 29 disciplines reminiscent of the courses. The result showed that the relationship between Society, Environment and Health is discussed in an inseparable way and presents an increasing evolution in the literature, since its concepts are too much to discuss the cause and effect of a certain outcome. Although, at the local level, standardized courses such as "technological" presented a formative profile equidistant to the macro-tematic, due to insufficient disciplines with economic-social-environmental approaches. However, this perspective that opens from connected studies through an integrative review is still fairly contemporary. In this current panorama of political changes, above all, managing a humanitarian crisis, there is a need for interdisciplinary studies and integrated approaches in the analysis and solution of problems of Environment and Health, mainly in the Amazon.